Keep it Simple: Ceramic Kelvin Cells via Liquid Crystal Display-Stereolithography Printing - Simon, Swantje; Hoffmann, Patrizia; Stötzel, Tim; Weber, Jonas; Fey, Tobias (Advanced Engineering Materials, 2024)
Additive manufacturing is the state-of-the-art method for producing complex ceramic parts. For cellular materials, the freedom of design is particularly advantageous, as pore networks and shapes can be tailored. Herein, the direct printing of complex parts with high porosity using the cost-effective manufacturing method of Liquid Crystal Display-based stereolithography on low-cost printers is determined. It is investigated how the architecture of the alumina Kelvin cells topology, their fabrication process, the printing parameters, and the microstructure affect the accuracy and mechanical properties of the printed samples. A notable reduction to a strut thickness of Kelvin cells down to 0.20 mm is achieved corresponding to a reduction of 1.5 compared with the state-of-the-art literature (min. 0.35 mm). Ultrahigh porosities between 89.5% and 97.2% and a maximum compressive strength of 1.84 ± 0.17 MPa are reached due to the dense struts of the structure. Low-cost and simple vat ceramic photopolymerization with high accuracy printing proves to be a promising candidate for the rapid and cost-effective fabrication of highly porous and complex ceramic structures.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Kelvin cells; periodic structures; vat photopolymerization

The sound of porosity: Suitability of the impulse excitation technique (IET) to determine the Young's modulus of 2D macroporous ceramics - Stötzel, Tim; Funk, Swantje; Fey, Tobias (Open Ceramics, 2024)
The presence of pores in a ceramic leads to a lower Young's modulus compared to dense material. For the development of porous ceramics with tailored elastic properties, an exact determination of the Young's modulus is required, especially for industrial applications. Therefore, we investigated the suitability of the non-destructive impulse excitation technique for measuring the dynamic Young's modulus of two-dimensional ceramics with low porosity (P < 19 %). For rectangular samples it was shown that the measurement results depend on the geometric pore position, as added pores outside the nodal lines of the fundamental flexural vibration had no influence on the result. Pores in the inner part of the sample led to a decrease of the Young's modulus that is in good agreement with empirical and analytical models. For the investigated interval of porosity range, the influence of pore size and geometric position on the reduction of the Young's modulus was determined.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Impulse excitation technique; Porosity; Young's modulus